2016
DOI: 10.1002/oby.21698
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety independently contributes to elevated inflammation in humans with obesity

Abstract: Objective Anxious and depressive states are associated with increased cardiovascular disease (CVD) risk and a proinflammatory phenotype, although the latter appears to be at least partially explained by adiposity. We hypothesized that depression and anxiety would be associated with elevated inflammation independent of adiposity in persons with obesity at high risk of CVD. Methods We explored the relation between baseline anxiety as measured by the Beck Anxiety Inventory (BAI) and depression as measured by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
(36 reference statements)
1
25
3
4
Order By: Relevance
“… 7 9 , 40 Previous studies reported that anxiety symptoms were associated with increased levels of TNF-α, IL-6 and CRP. 8 , 9 , 41 Duivis et al also observed elevated serum CRP levels in a male population after adjusting for sociodemographic and lifestyle-related confounding factors in a large adult sample. 40 These previous results are inconsistent with our finding that the anxiety score was not associated with inflammation levels in a multivariate and stratified analysis.…”
Section: Discussionmentioning
confidence: 92%
“… 7 9 , 40 Previous studies reported that anxiety symptoms were associated with increased levels of TNF-α, IL-6 and CRP. 8 , 9 , 41 Duivis et al also observed elevated serum CRP levels in a male population after adjusting for sociodemographic and lifestyle-related confounding factors in a large adult sample. 40 These previous results are inconsistent with our finding that the anxiety score was not associated with inflammation levels in a multivariate and stratified analysis.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the present study found that obese patients had significantly more symptoms of depression than did underweight, eutrophic and overweight patients. The literature suggests that excess body weight is highly-associated with the appearance of anxiety and depression symptoms (41,42) . A recent study in Poland with patients with IBD also found significant results regarding overweight and higher levels of depressive symptoms (43) .…”
Section: Discussionmentioning
confidence: 99%
“…The cause of this phenomenon is seen in the inflammatory system that is modulated by obesity [26]. It was found that in a group of 10,348 women, BMI was positively correlated with mild to moderate depressive disorders and also with high levels of depression.…”
Section: Discussionmentioning
confidence: 99%
“…It includes low self-esteem, the feeling of being stigmatised, or disturbances in employment and relationships [25]. Likewise, the deterioration of the disease, which results from the elevated inflammatory response, related to both anxiety and depression, may account for the poorer outcome of quality of life questionnaires [26].…”
Section: Discussionmentioning
confidence: 99%